Pemetaan Kapabilitas Relasional dalam Studi Bisnis: Tinjauan Literatur Sistematis terhadap Tren Penelitian 2013–2023 - Maria Augustine Graciafernandy; Augusty Tae Ferdinand (Society, 2024)
Building and maintaining effective relationships is crucial for business success. Therefore, this study reviews existing research and provides a comprehensive overview of relational capability (RC). Recognizing the importance of RC, this study conducts a systematic literature review (SLR) by analyzing 221 articles from the Scopus database (2013–2023) using the Publish or Perish software. After applying specific selection criteria, 83 articles focusing on RC were chosen for in-depth analysis. The findings reveal significant gaps in RC research, particularly in terms of theoretical approaches, methodologies, and contextual applications, which offer opportunities to enrich the existing body of knowledge. The study emphasizes that RC skills—such as communication, empathy, trust-building, conflict resolution, and collaboration—are essential for sales professionals to understand customer needs, build strong relationships, and achieve sales targets. This study contributes to the understanding of relational capability by integrating various theoretical frameworks and employing quantitative, qualitative, and mixed methods. It offers a comprehensive overview of organizational interactions and their implications for sustainable growth and competitive advantage.